Smoking cessation for improving mental health - Taylor, GMJ; Lindson, N; Farley, A; Leinberger-Jabari, A; Sawyer, K; te Water Naudé, R; Theodoulou, A; King, N; Burke, C; Aveyard, P (Cochrane Collaboration, 2021)
Background: There is a common perception that smoking generally helps people to manage stress, and may be a form of 'self‐medication' in people with mental health conditions. However, there are biologically plausible reasons why smoking may worsen mental health through neuroadaptations arising from chronic smoking, leading to frequent nicotine withdrawal symptoms (e.g. anxiety, depression, irritability), in which case smoking cessation may help to improve rather than worsen mental health.